Pendidikan Kebangsaan Dalam Pesantren Perspektif Abdul Wahid Hasyim - Umi Musaropah (Universitas Cokroaminoto Yogyakarta, 2019)
This educational history research is focused on the life, activities and thoughts of KH. A. Wahid Hasyim, a national hero of independence in developing national education in pesantren, an environment which he never left from birth to adulthood. In pesantren Tebuireng run by his family, he began to study and also applied his educational ideas. His contribution expanded to the national level after being involved in NU and national activities in his lifetime to serve as minister of religion including broadening understanding of Islam and its institutionalization in state activities. The idea of national education is based on the belief that the more languages mastered by students, the stronger the sense of nationalism in them. This needs to be balanced with the strengthening of local culture and religion in daily life.